2013
DOI: 10.3109/09638288.2013.788219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a film portrayal of a police officer with spinal cord injury on attitudes towards disability: a media effects experiment

Abstract: Restrictions in participation may result from an interaction of persons with impairments with an environment that is dominated by negative attitudes towards disability The portrayal of disabled people in the media can influence the public's attitudes towards disability in both positive and negative ways In this experimental study, attitudes of the general public were significantly improved following viewing a short film featuring a positive media portrayal of a police officer with paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We obtained a convenience sample, which was accessible to us during the daytime at the university. The results of previous studies tended to support the notion that public media would have a general impact on viewers' attitudes toward PWDs regardless of their educational levels and fields of study (Farnall & Smith, 1999;Ferrara et al, 2015;Reinhardt et al, 2014;Safran, 1998). Accordingly, we believe that the results of this study are informative in regard to undergraduate and graduate education across various majors.…”
Section: Participant Recruitment and Sample Characteristicssupporting
confidence: 55%
“…We obtained a convenience sample, which was accessible to us during the daytime at the university. The results of previous studies tended to support the notion that public media would have a general impact on viewers' attitudes toward PWDs regardless of their educational levels and fields of study (Farnall & Smith, 1999;Ferrara et al, 2015;Reinhardt et al, 2014;Safran, 1998). Accordingly, we believe that the results of this study are informative in regard to undergraduate and graduate education across various majors.…”
Section: Participant Recruitment and Sample Characteristicssupporting
confidence: 55%
“…The way media (television and film) portrays disabilities has been found to influence perceptions and understandings of disability (Samsel and Perepa 2013). The use of film to depict employed disabled persons (in the cited research the film featured a police officer with paraplegia) has been successful in increasing nondisabled participants' ratings of eligibility and employment rates of disabled persons (Reinhardt, Pennycott, and Fellinghauer 2014). An earlier study found that paid advertising could be used to successfully modify beliefs underlying racial discrimination in employment of indigenous peoples (Donovan and Leivers 1993).…”
Section: Discussionmentioning
confidence: 96%
“…This article suggests an interrupter (Williams 2014) technique that is more in line with advertising (Reinhardt, Pennycott, and Fellinghauer 2014;Samsel and Perepa 2013;Donovan and Leivers 1993): such an approach uses media to perhaps more subtly overwrite mental models that may be held by the general population, thereby enriching and expanding what we hold to be prototypical members or employees of the library staff. In doing so we can make the invisible debilities of these models-"invisible" because they are unacknowledged-into visible abilities of underrepresented groups now visualized as a range of possible employees successfully fulfilling a range of positions in our country's libraries.…”
Section: Discussionmentioning
confidence: 96%
“…These include ethnic minorities, such as native Americans (Rollins & O'Connor, 1998), and various kinds of disabilities (Safran, 1998a(Safran, , 1998bArokiasamy, 1996), such as epilepsy (Kerson et al, 2000). There is also representation of some functional or occupational groups: female athletes (Wuestenberg & Todd, n.d.), archivists (Oliver & Daniel, 2015), lawyers (Beard, 2011) and policemen (Reinhardt et al, 2014), as well as political and religious groupings: Communism (Khouri, 2007), radical Islamists (Fachinger, 2011), and the Klu Klux Klan (Dessommes, 1999). More general themes include the tobacco industry (Dixon et al, 2001) and modernist architecture (Heathcote, 2000).…”
Section: )mentioning
confidence: 99%
“…More general themes include the tobacco industry (Dixon et al, 2001) and modernist architecture (Heathcote, 2000). In a few cases the research involves the testing of public response to the depiction of the theme (Dixon et al, 2001;Reinhardt et al, 2014), but in most studies the methodology consists simply of narrative content analysis. In several of the papers (Beard, 2011;Dessommes, 1999;Dixon et al, 2001) there is no explicit methodology, but the portrayal of the topic is clearly based on narrative aspects of the plot and the observed personality of the characters.…”
Section: )mentioning
confidence: 99%